Regulation effect of miR-7 on intervening colorectal cancer rats with HP infection through Akt/GSK-3β/β-catenin pathway : Effect of miR-7 on intervening colorectal cancer pathway - Su, Xin; Wang, Wenbin; Ma, Siyang; Ning, Huahan; Chen, Jiaxi (Cellular and Molecular Biology, 2022)
This experiment aimed to analysis of the intervention effects of modulating miR-7 on rats with colorectal cancer complicated with HP infection and the effects on (serine/threonine kinase) Akt / (glycogen synthase kinase 3 β） GSK-3 β/ （ β- β - Catenin) β- Influence of the catenin pathway. For this purpose, forty special pathogen-free (SPF) - grade rats of both sexes were randomly divided into 10 control, 10 colorectal cancer and HP infection model groups, 10 up-regulated miR-7, and 10 down-regulated miR-7 groups. Observational analysis of rat colon tissues was performed using the HE staining method. Detection of inflammatory factors [TNF- α、 IL-8, IL-6], detection of miR-7 expression, detection of Akt, GSK-3 using Western blot β、β- Catenin protein expression. Results showed that forty special pathogen-free (SPF) - grade rats of both sexes were randomly divided into 10 control, 10 colorectal cancer and HP infection model groups, 10 up-regulated miR-7, and 10 down-regulated miR-7 groups. Observational analysis of rat colon tissues was performed using the HE staining method. Detection of inflammatory factors [TNF- α、 IL-8, IL-6], detection of miR-7 expression, detection of Akt, GSK-3 using Western blot β、β- Catenin protein expression. It was concluded that modulation of miR-7 in rats with colorectal cancer and HP infection enables regulation of the Akt / GSK-3 β/β- Catenin pathway to improve serum inflammation condition and alleviate HP infection in rats, which played a better role in intervention.